Development of Environmental Friendly Antifouling Coatings - Liu, Li-Ping; Hou, Bao-Rong (Asian Journal of Chemistry, 2014)
Marine structures such as platforms, jetties and ship hulls are subject to diverse and severe biofouling. This article introduces briefly the process and damage in respect of marine biofouling. The use of antifouling coatings for protection from the marine environment has a long history. By considering the historical and current approaches to antifouling systems, this paper presents the use of modern approaches to the design of an environmentally acceptable, broad spectrum antifouling system for a large ship' s hull.